Repeated CMV Infection in a Heart Transplantation Patient - Josep Melero-Ferrer; Ignacio J. Sanchez-Lazaro; Amparo Navea-Tejerina; Luis Almenar-Bonet; Marino Blanes-Julia; Luis Martinez-Dolz; Antonio Salvador-Sanz (Case Reports in Transplantation)
Infections are one of the leading causes of morbidity and mortality in heart transplantation (HTx). Cytomegalovirus (CMV) is the most common viral infection during the first year after HTx, but it is more unusual after this time. We present the case of a patient who underwent an HTx due to a severe ischemic heart disease. Although the patient did not have a high risk for CMV, infection, he suffered a reactivation during the first year and then up to six more episodes, especially in his eyes. The patient received different treatments against CMV and the immunosuppression was changed several times. Finally, everolimus was introduced instead of cyclosporine, and mycophenolate mofetil was withdrawn. The presented case provides an example of how the immunosupresion plays a key role in some infections in spite of being a suitable antiviral treatment.